Psoriasis in Obese Adolescents with Diabetes—From Common Molecular Background to Vicious Circle of Metabolic Syndrome—Case Report and Review of Literature - Angelika Bielach-Bazyluk; Filip Bossowski; Magdalena Skorupska; Hanna Mysliwiec; Artur Tadeusz Bossowski; Iwona Flisiak (Cells)
Psoriasis and type 1 diabetes mellitus (T1DM) are chronic autoimmune diseases sharing common immunological pathways, particularly the involvement of interleukin 17 (IL-17), driving Th17-mediated inflammation. This review explores the overlap between psoriasis, obesity, T1DM, and necrobiosis lipoidica (NL), a skin condition associated with diabetes. Obesity exacerbates inflammation through immune cell activation in adipose tissue and the release of proinflammatory adipokines, such as leptin, resistin, and IL-18, which enhance autoimmune responses and insulin resistance. Leptin promotes the differentiation of Th1 and Th17 cells, which are central to autoimmune responses in both psoriasis and T1DM. The coexistence of psoriasis, T1DM, and insulin resistance further complicates metabolic control, increasing the risk of complications like diabetic nephropathy and cardiovascular disease. Biologic treatments targeting IL-17A and IL-17F offer promising therapeutic options for managing both skin and metabolic symptoms. The early identification and management of metabolic risk factors, along with personalized interventions, are essential to improve clinical outcomes in patients with psoriasis and T1DM, particularly in obese individuals. This case report and review highlight the complex interplay of these conditions and emphasize the need for integrated treatment strategies.